Development, and genetic and metabolic characterization of new tomato mutants with enhanced and deficient carotenoid content. Issue 5 (3rd September 2017) - Dan, Yinghui; Yousef, Gad; Campbell, Faith N.; Phelps, Drake W.; Burnett, Callie; Kekkonen, Anni; Shockley, Alexa; Lila, Mary Ann
ABSTRACT: Tomato ( Solanum lycopersicum ) is a valuable vegetable crop rich in health-protective carotenoids, but breeding improvements are limited by its narrow genetic diversity. New mutants with enhanced and deficient carotenoid content in a single genetic background of tomato cv. MicroTom were developed via chemical mutagenesis. Genetic and metabolic analyses showed that mutant DC260, which exhibited fruit color alteration from red to deep red interlaced with orange color, had significant (P < 0.05) increases of lycopene (up to 42.8%) and ß-carotene (up to 61.5%) compared with control plants. Pearson correlation analysis of M1 and M2 generations in DC260 revealed that fruit color alteration was significantly (P < 0.05) correlated with lycopene (coefficient = 0.55) and ß-carotene content (coefficient = 0.63). The fruit color alteration of DC260 was controlled by a single gene at a heterozygous locus. In contrast, mutant DC107 and DC624, which exhibited fruit color alteration from red to orange-yellow, was significantly (P < 0.05) carotenoid-deficient with up to 346.3-, 10.8-, and 185.2- fold reductions of lycopene, ß-carotene, and total carotenoids, respectively, compared with the control plants. Carotenoid deficiency in DC170 and DC624 was responsible for the fruit color alteration and was controlled by a dominant gene at a homozygous locus.